FOREIGN INVESTMENT: CONVENIENCE ADN LEGAL PROTECTION FOR INVERSTOR - Fakhri Muhammad Novendra (Jurnal Ilmiah Advokasi, 2024)
President Joko Widodo's administration has made every effort to increase the value of foreign direct investment, data of foreign direct investment’s growth has also shown a significant increase, but has foreign direct investment that is predicted to be able to become the backbone of Indonesia in breaking away from becoming a developing country has been properly accommodated? Foreign direct investment requires legal certainty which will spread to all parts of the foreign direct investment process. Therefore, legal certainty is one of the main factors for a country to attract foreign direct investment capital into the a country. There is a need for broader and comprehensive legal certainty to ensure that foreign investors can be guaranteed from a legal perspective to do business and build Indonesia together. Not only legal certainty in the investment sector, but also other domestic legal certainty related to the investment climate, one of the most important is environmental law relating to sustainable development. This article will discuss the basics of foreign direct investment, the importance of foreign direct investment, factors attracting foreign direct investment, President Joko Widodo's new policies and regulations on foreign direct investment, current data of the realization of foreign direct investment and investor’s consideration to ensure themselves and their initial funds of their investment is safe as long as they invest in Indonesia. Keywords:  Foreign Direct Investment, economy policies, legal certainty